Optical density of high fluence autoradiographic images to study boron microdistribution: validation of the technique in tissue sections - Espain, M. S.; Viglietti, J. S.; Vidal, C.; Martin, D.; Trivillin, V. A.; Monti Hughes, A.; Palmieri, M. A.; De Leo, L.; Garabalino, M. A.; Curotto, P.; Thorp, S. I.; Pozzi, E. C. C.; et al. (Frontiers in Nuclear Engineering, 2024)
The distribution of boron in biological samples coming from BNCT protocols can be determined by the analysis of autoradiographic images formed by nuclear tracks on polymeric detectors.The tissue section is first explored to delimit regions of interest (ROIs), and then it is removed in order to reveal nuclear tracks through an etching process. A quantitative autoradiographic technique was developed to measure the boron concentration in the sample by counting the nuclear tracks on the detector. However, under certain circumstances, rapid measurements of boron distribution are required. For that purpose, a methodology was developed, allowing a rapid and easy determination of boron concentration and distribution in a tissue section by measuring grey levels in the corresponding high fluence autoradiographic image (HFA). The grey levels are then converted to optical density values which are then correlated with boron concentration values.In order to validate the technique, consecutive sections of several tissue samples were analyzed by the conventional counting method and by HFA. The image analysis and boron concentration estimation can be carried out in under 15 minutes, and relative differences between zones can be easily determined.